A 31-Year-Old Man with Primary Hyperparathyroidism Due to Parathyroid Adenoma: A Case Report - Rahman, Md Mahfuzer; Faruquey, Zeenat; Rabbani, Golam; Ban, Akter; Azad, Mdabulkalam; Kabir, Md Jahangir (Bangladesh Journal of Medicine, 2024)
Primary hyperparathyroidism (PHPT) is an endocrine disorder characterized by chronic elevation of serum concentrations of calcium and parathyroid hormone (PTH). The most frequent forms of clinical presentation are symptomatic renal or skeletal disease with moderate or severe hypercalcemia. The biochemical profile of PHPT is characterized by hypercalcemia and high or inappropriately normal PTH concentrations. Parathyroidectomy is the only definitive cure. Medical treatment with the calcimimeticcinacalcet has been shown to normalize calcemia in a high percentage of cases. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 180-181